2015
DOI: 10.1097/aln.0000000000000567
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of MicroRNA-21 Mediates Isoflurane-induced Protection of Cardiomyocytes

Abstract: Background Anesthetic cardioprotection reduces myocardial infarct size following ischemia-reperfusion injury. Currently, the role of microRNA in this process remains unknown. MicroRNAs are short, non-coding nucleotide sequences that negatively regulate gene expression through degradation or suppression of messenger RNA. In this study, we uncovered the functional role of microRNA-21 (miR-21) upregulation after anesthetic exposure. Methods MicroRNA and messenger RNA expression changes were analyzed by quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
4
33
1
Order By: Relevance
“…Recently, we have indicated that PDCD4 is a down-stream target of miR-21 in ISO-induced protection of cardiomyocytes. 20 Thus, ISO-induced up-regulation of miR-21 may alter the expression of multiple gene targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have indicated that PDCD4 is a down-stream target of miR-21 in ISO-induced protection of cardiomyocytes. 20 Thus, ISO-induced up-regulation of miR-21 may alter the expression of multiple gene targets.…”
Section: Discussionmentioning
confidence: 99%
“…In rat hearts or neonatal rat cardiomyocytes, our array analyses of microRNAs indicate that ISO up-regulated 11 out of 87 microRNAs studied, including miR-21, microRNA-210, and microRNA-30 family. 20 It is likely that multiple microRNAs are involved in the cardioprotective effect of ISO. However, miR-21 plays an important role in protection of cardiomyocytes against hypoxia/reoxygenation injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 H9C2 cardiac myoblast cells (ATCC) were transfected with anti-scr or anti–miR-21-5p (40 nM, Exiqon, Vedbaek, Denmark), as previously described. 60 After 48 hours, cells were treated with insulin-like growth factor-1 (50 ng/ml; StemRD, Burlingame, CA) or saline vehicle for an additional 24 hours ( N = 3 per group). Cells were fixed and imaged.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal rat cardiomyocytes were transfected with 20 nM pre-miR-21-5p or scr control ( N = 3 per group) (ThermoFisher) as previously described 60 and collected 48 hours later. Tissue and cell material were processed for Western blot analysis as previously described, with quantification of Coomassie staining used as to normalize protein loaded.…”
Section: Methodsmentioning
confidence: 99%